2009
DOI: 10.1177/0885728809338714
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Computer-Assisted Instruction on Students’ Knowledge of Postschool Options

Abstract: Enhancing students' ability to make informed choices is an important precursor to successful choice-making, decision-making, and goal-setting. This study used a multiple-baseline design across behaviors replicated across participants to examine the effects of computer-assisted instruction on acquisition of students' knowledge of postschool options (i.e., employment, education, independent living). Results demonstrated a functional relationship between baseline and intervention for all four students. Implicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Eleven of the 17 research studies that focus on assistive technology used students with an intellectual disability and 41% of those studies were published in Education and Training in Autism and Developmental Disabilities . Multiple articles examined the use of computer-assisted instruction (CAI) to improve involvement in self-directed individualized education programs (IEPs; Kelley, Bartholomew, & Test, 2013), knowledge of postschool options (Mazzotti, Test, Wood, & Richter, 2010), and comprehension of transition planning for parents of young adults with a disability (Rowe & Test, 2010). Several articles evaluated handheld devices to improve independent living skills.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven of the 17 research studies that focus on assistive technology used students with an intellectual disability and 41% of those studies were published in Education and Training in Autism and Developmental Disabilities . Multiple articles examined the use of computer-assisted instruction (CAI) to improve involvement in self-directed individualized education programs (IEPs; Kelley, Bartholomew, & Test, 2013), knowledge of postschool options (Mazzotti, Test, Wood, & Richter, 2010), and comprehension of transition planning for parents of young adults with a disability (Rowe & Test, 2010). Several articles evaluated handheld devices to improve independent living skills.…”
Section: Resultsmentioning
confidence: 99%
“…This study suggests the use of SACD, as a CAI, is a promising transition practice to teach student participation in the IEP planning process (Mazzotti et al, 2013(Mazzotti et al, , 2014NTACT, 2016;Test et al, 2015). Educators seeking to foster their students' self-advocacy skills by using the SACD can take advantage of the shorter teacher time it requires to implement when compared to live instruction format of the strategy, its ability to supplement instruction, and its accessibility to support student use independently (Lancaster et al, 2002;Mazzotti, Test, Wood, & Richter, 2010). However, students in the treatment group improved on their Self-Advocacy Self-Report Total and Question 1 scores following a total instructional time of 7.5 hr across 2 weeks.…”
Section: Implications For Practicementioning
confidence: 94%
“…Mazzotti et al (2010) suggested that computer-assisted instruction can be used to increase students' knowledge of post school outcomes and methods for improving post school success.…”
Section: Transitions and Post School Outcomesmentioning
confidence: 99%